Schlaglichter historischer Forschung. Studien zur deutschen Geschichte im 19. und 20. Jahrhundert - Borowsky, Peter (Hamburg University Press, 2005)
Peter Borowsky (1938-2000) was a committed historian and enthusiastic historian. For more than 30 years he taught modern history at the History Department of the University of Hamburg. He left a lasting mark on generations of students through his competence and his way of conveying history in a lively way. This is also evident in the 14 contributions to German history in the 19th and 20th centuries, which are published here for the first time. The topics range from the Hohenzollern region to the political culture of the Federal Republic of Germany and include students in the revolution of 1848, Hamburg's 19th century history, the development from the Weimar Republic to the "Third Reich", German relations with Eastern European countries and the USA. Two texts deal vividly with the history of German historiography and the "Historian's Dispute".